THE IMPORTANCE OF MODERN TECHNOLOGIES IN EXTENDING THE SERVICE LIFE OF ASPHALT CONCRETE PAVEMENTS - Tilakov Sukhrob Mukhammadiyevich; Urolmamatov Asadbek Bobomurod ugli; Nurullayev Sunnat Sirojiddin ugli (European Science Publishing, 2025)
This article discusses asphalt concrete pavement as the primary construction element widely used in road building. It is worth noting that almost all roads in Uzbekistan are made of asphalt concrete. This fact indicates a high demand for asphalt concrete pavement in our country. Consequently, the quality and long-term durability of asphalt concrete pavement are crucial. It should be emphasized that during extended use, the quality of asphalt concrete pavement can deteriorate due to climatic conditions, heavy vehicle loads, and improper application. This article presents the problems that arise in asphalt concrete pavement and analyzes them. It also outlines technologies for addressing existing issues with asphalt concrete pavements by implementing temporary restrictions on truck traffic during hot summer temperatures.
Keywords: Asphalt concrete, reconstruction, bitumen, temperature-induced cracks, load, drainage system, trucks, upper load limit, deformation, pavement, service life.